Kohesi dan Koherensi dalam Karangan Mahasiswa Program In-Country Tahun 2018-2019 - Muhammad I’tishom (Universitas Negeri Malang, 2021)
Abstract: This research aims to describe the use of cohesion and coherence in Thai students’ papers. This research uses qualitative methods. The data of this research are in the form of cohesion and coherence. The data source of this research are Thai students’ final papers. The data were then analyzed using description, interpretation, and explanation. The results of this research show two concerns as follows. First, the use of cohesion markers in student papers including grammatical cohesion (conjunctions and references) and lexical conjunctions (repetition, synonyms, antonyms, hyponyms, and collocations). Second, the coherence markers used include marked coherence (causality, contrast, additive, temporal, chronological, intensity, and sequence) and unmarked coherence (details and data organization). Based on the results and discussion, it was concluded that these Thai students of In-Country program in 2018/2019 could use limited cohesion and coherence in writing Indonesian papers. Keyword: cohesion, coherence, BIPA, student writing, BIPA student. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan pemakaian kohesi dan koherensi dalam karangan mahasiswa Thailand yang belajar bahasa Indonesia. Penelitian ini menggunakan rancangan kualitatif. Data penelitian berupa bentuk-bentuk kohesi dan koherensi. Data penelitian bersumber dari sejumlah makalah tugas akhir mahasiswa. Data penelitian dianalisis dengan cara melakukan deskripsi, interpretasi, dan eksplanasi. Hasil penelitian menunjukkan dua hal sebagai berikut. Pertama, pemakaian penanda kohesi dalam karangan mahasiswa mencakup kohesi gramatikal (konjungsi dan referensi) dan konjungsi leksikal (repetisi, sinoni, antonim, hiponim, dan kolokasi). Kedua, penanda koherensi yang digunakan mencakup koherensi berpenanda (kausalitas, kontras, aditif, temporal, kronologis, intensitas, dan perurutan) dan koherensi tidak berpenanda (perincian dan perian). Berdasarkan hasil dan pembahasan disimpulkan mahasiswa Thailand program In-Country tahun 2018/2019 mampu menggunakan kohesi dan koherensi secara terbatas dalam menulis karangan bahasa Indonesia. Kata kunci: kohesi, koherensi, BIPA, karangan, mahasiswa BIPA.